Eﬀect of two diﬀerent types of exercise volumes on exercise capacity, physical activity, and quality of life in subjects undergoing percutaneous coronary intervention: a pilot study - Angarita-Fonseca, Adriana; Jácome-Hortúa, Adriana Marcela; Ortiz-Patiño, Andrea Juliana; Rincón-Rueda, Zully Rocío; Villamizar-Jaimes, Carmen Juliana; Paredes-Prada, Erika Tatiana; Sánchez-Delgado, Juan Carlos (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Phase II of cardiac rehabilitation includes 36 sessions of exercise over 12 weeks, an intervention format that seems to be based on historical practice and not scientiﬁc evidence. The objective was to evaluate the eﬀect of two types of exercise vol-umes on exercise capacity, physical activity levels, and quality of life in subjects undergoing percutaneous coronary intervention.Methods. A randomized controlled clinical trial was performed in 17 subjects, who were randomly assigned into two groups. The ﬁrst (n = 7) was trained for eight consecutive weeks, and the second (n = 10) for 12 weeks. The six-minute walk test, the In-ternational Physical Activity Questionnaire, and the SF-36 were applied before starting the cardiac rehabilitation program at 8 and 12 weeks.Results. No signiﬁcant diﬀerences were found between the intervention groups. The rise in VO2 max was only signiﬁcant in the 8-week group. Both groups improved their distance walked and sedentary behaviour. The 12-week intervention group had improved the quality of life, speciﬁcally in physical functioning, and the 8-week intervention group in the domains of social, physical, and emotional functioning. Additionally, the percentage of participants meeting physical activity recommendations was higher in the 12-week cardiac rehabilitation group.Conclusions. The implication for clinical practice is that the exercise traditionally used in cardiac rehabilitation shows early changes in exercise capacity and quality of life. The results of the levels of physical activity and sedentary behaviour improved after 12 weeks of rehabilitation without the presence of adverse events.
Keywords: physical ﬁtness; myocardial infarction; secondary prevention; cardiac rehabilitation; angioplasty